Creating Islamic art with interactive geometry software - Ismail, Zaleha; Kasmin, Mohd. Khalid (Persatuan Teknologi Pendidikan Malaysia, 2007)
The production of images, in particular figurative art is discouraged in Islam on the basis that it could lead to idolatry. For the Muslims there is no divinity other than the Almighty God and this means that no any form of creations can be projected to His attributes. In this way, muslim artists express their works in creating patterns of complex geometric designs as well as intricate patterns of vegetative ornament. These masterpieces have covered the surfaces of buildings especially mosques, palaces and other public places in replace to human figures as established in the non-Muslim culture. From the mathematical perspective, the distinctive Islamic art has cleverly combined the use of common geometric shapes such as circles, points and lines together with some geometric principles such as symmetry, similarity and transformation, namely translation, rotation, reflection and scaling. With the present software technology, the creation of this art can be made easier using interactive geometry software (IGS) which is also known as dynamic geometry software (DGS). IGS are computer programs which allow their users to interactively create, manipulate and explore geometric constructions using points, lines, circles and geometric principles. Activities involving students to create Islamic art with IGS will help them to appreciate mathematics as an art that is enjoyable and fun besides realizing that its development is greatly influenced by values and cultures. This paper will describe how some basic designs can be constructed using KDE interactive geometry (KIG) which is available as free open source software (FOSS). Some samples of creative students' work will also be shared.